Caracterização funcional e estrutural de uma toxina de serpente brasileira com ação na hemostasia - Sousa, Bruna Barbosa de (2013)
Bothrops snakes are targets of studies in Brazil due to its geographical distribution and accidents occurrence. They are responsible for the most serious cases of snakebite in the country. Bothrops envenomations are often associated with complex local and systemic manifestations, including pain, edema, local hemorrhage, myonecrosis, hemostatic disorders, systemic bleeding and cardiovascular disorders. Snake venoms comprise a complex mixture of proteins and peptides and low molecular mass organic and inorganic components. The protein fraction comprises aminotransferases, acetylcholinesterases, hyaluronidases, L-amino acid oxidases, phospholipases A2, metalloproteinases, serine proteases, lectins, disintegrins, among others. Some of these protein components, enzymatic or non-enzymatic, are able to hydrolyse components of the extracellular matrix, activate or inhibit blood coagulation factors and interact with platelet receptors, causing hemostatic disorders such as incoagulability, hemorrhage and thrombosis. Due to their medical interest, these hemostatically active components have been isolated from snake venom and studied as potential therapeutic targets for the treatment and diagnosis of thromboembolic diseases. The present study aimed to purify and characterize a toxin from Bothrops moojeni snake venom. The characterization included: evaluation of its purity and molecular mass, N-terminal sequencing, determination of its proteolytic activity upon azocasein and fibrinogen, characterization of its hemorrhagic, anticoagulant and coagulant activities, characterization of its activity upon platelet aggregation and induction of pain and edema. The objectives were resolved and resulted in the isolation of a platelet aggregation inhibitor, designated Bmoo-Agg. The toxin showed a specific inhibitory effect on platelet aggregation induced by epinephrine and ristocetin in human platelet-rich plasma.